Remains of the Body in the Classical Hollywood Musical - Benet, Vicente (Cinémas)

(untitled) (Cinémas, 1996)
The human body, its role and configuration in Classical Hollywood cinema, offers a condensed view of the tension to be observed between narrative and spectacle in film. With the revival of the musical genre in the mid-1930s as our starting point, this paper proposes to analyze the human body as it relates to narration, montage and mise en scène. Observations are based on examples from various scenes in the film The Gay Divorcee (Mark Sandrich, 1934).